The Role of Islamic Micro Finance in Promoting Sustainable Development Goals (SDGs) in Indonesia - Abdul Wahab; Ilma Mahdiya (International Journal of Economics and Management Sciences, 2025)
Islamic Micro Finance (IMF) has an important role in supporting the Sustainable Development Goals (SDGs) in Indonesia by providing inclusive financial access based on sharia. This study aims to analyze how the IMF contributes to poverty alleviation (SDG 1), increasing financial inclusion (SDG 9), reducing economic inequality (SDG 10), promoting sustainable economic growth (SDG 8) and improving financial education and awareness (SDG 4). The research method used is a qualitative descriptive approach with literature analysis and case studies from several sharia microfinance institutions in Indonesia. The research results show that the IMF through instruments such as qardhul hasan, mudharabah, musyarakah, and ZISWAF is able to provide financial solutions for poor community groups and micro businesses. In addition, the digitalization of sharia financial services further increases the IMF's reach in supporting financial inclusion. However, there are challenges that still need to be overcome, such as limited capital, low sharia financial literacy, and regulations that are not yet optimal. Therefore, strengthening regulations, sharia financial education and Islamic financial technology innovation are key strategies for optimizing the IMF's role in achieving the SDGs in Indonesia. This study provides an original contribution by highlighting the strategic role of Islamic Micro Finance in achieving SDGs in Indonesia through a sharia-based approach. The added value of this study lies in the integration between Islamic financial instruments and sustainable development goals, as well as the importance of digital innovation and financial education in the local context.